1991
DOI: 10.7326/0003-4819-114-10-840
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking: Risk Factor for Premature Facial Wrinkling

Abstract: Cigarette smoking is an independent risk factor for the development of premature wrinkling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
142
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(161 citation statements)
references
References 11 publications
15
142
0
4
Order By: Relevance
“…[1][2][3][4][5][6][7] In this study we have shown that severe facial wrinkling (Daniell score >IV) is significantly associated with a lower mean FEV 1 and COPD. Indeed, more than 80% of smokers with facial wrinkling fulfilled the spirometric criteria for COPD.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] In this study we have shown that severe facial wrinkling (Daniell score >IV) is significantly associated with a lower mean FEV 1 and COPD. Indeed, more than 80% of smokers with facial wrinkling fulfilled the spirometric criteria for COPD.…”
Section: Discussionmentioning
confidence: 92%
“…Individuals were classified as wrinkled using a method similar to that previously described by Kadunce et al 2 The median wrinkle score in our study group was II (IQR 1). For the analysis we classified those individuals in the 90th centile (Daniell score >IV) as wrinkled and those with scores of ,IV as unwrinkled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of UVR-induced and accelerated aging are discussed later in this review. The second most important driver of extrinsic aging is cigarette smoking [24][25][26][27][28] .…”
Section: Extrinsic Agingmentioning
confidence: 99%
“…Smoking has long been known to affect skin appearance, in particular by promoting facial skin wrinkling (Daniell 1971;Kadunce et al 1991;Koh et al 2002;Patel et al 2006). The effect is enhanced by sunlight (Yin et al 2001), but alterations of elastic tissue properties also occur in sunprotected areas (Frances et al 1991;Helfrich et al 2007).…”
Section: Discussionmentioning
confidence: 99%